2006
DOI: 10.1021/pr0603250
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Related to Analysis of Protein Spot Volumes from Two-Dimensional Gel Electrophoresis As Revealed by Replicate Gels

Abstract: Assumptions that need to be considered prior to statistical analysis of protein spot volumes from two-dimensional gel electrophoresis (2-DE) data are studied using replicate gels of the same sample. The most important observation is that the data tables of protein spot volumes from 2-DE images contain a large number of missing values, which are not consistent with the presence or absence of the proteins. This implies both loss of information and problems for the subsequent statistical analysis. Challenges with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 20 publications
1
46
0
2
Order By: Relevance
“…On the other hand, most recent publications (Millioni et al 2010a;Silva et al 2010;Dowsey et al 2006;Grove et al 2006;Berth et al 2007;Clark and Gutstein 2008) are in agreement in concluding that 4th generation pixel-based software workflow (Fig. 1) has some advantages over spotbased software, as explained in the following sections.…”
Section: Software-related Variabilitysupporting
confidence: 73%
“…On the other hand, most recent publications (Millioni et al 2010a;Silva et al 2010;Dowsey et al 2006;Grove et al 2006;Berth et al 2007;Clark and Gutstein 2008) are in agreement in concluding that 4th generation pixel-based software workflow (Fig. 1) has some advantages over spotbased software, as explained in the following sections.…”
Section: Software-related Variabilitysupporting
confidence: 73%
“…Matching 2-DE patterns of gliadins from different varieties, therefore, is a challenging matter, as there is a risk that a large proportion or in fact all the proteins may be different. This is also the reason why we set zeros when proteins were not detected, although there is a risk that failure to detect proteins may result from mismatch of proteins rather than the absence of proteins [25]. Despite these challenges, the different strategies were able to unravel the same underlying pattern in the data.…”
Section: Discussionmentioning
confidence: 99%
“…The pitfalls of erroneously estimated spot volumes and inserted missing values are lately well described by Faergestad et al [9]. The number of spots containing a missing value in a match set can be quite large, as shown in a recent study by Grove et al [10]. It was found that as much as 80% of the spots collected in the match table for analysis are subject to missing values.…”
Section: Introductionmentioning
confidence: 90%